Sustainability: Beware of Greenwashing - Teng, Paul (2017)
The Sustainable Development Goals (SDGs) were endorsed by the global community through the UN in late 2015. Sustainability reporting has become a business, and there is evidence of some degree of “Greenwashing”. Walking the talk is more important and convincing of commitment than elaborate reports with quantitative metrics.